IDENTIFIKASI KLASTER INDUSTRI KECIL DAN MENENGAH SEBAGAI UPAYA PENGEMBANGAN EKONOMI LOKAL KOTA SEMARANG - Ferowati Raharjo (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
To promote economic growth, namely the development of the local economy. In encouraging the development of local economy by encouraging the growth of one cluster. Cluster is a systematic approach in developing SMEs. This study aims to classify and identify potential clusters of SMEs and SME cluster development strategy to assess the industry in the city of Semarang. Data analysis method used in this research is descriptive statistics to classify SMEs by type and location, Geographical Information System to identify potential clusters. The results showed that by grouping industries according to the type and location of the resulting four districts namely Genuk, Mijen, Semarang Semarang West and Central have similar types of industries and are at the same location. From the results of clustering are then identified potential cluster found four clusters that can be recommended that the furniture cluster in District Genuk, Mijen District and Western District of Semarang and food processing cluster in Semarang District Central this is supported by similar industry and inter-related and location potentially be contiguous clusters. Industrial cluster development strategy that is appropriate to the award of facility development, human resource development, equipment and marketing assistance through the promotion and exhibition at provincial level.